The low contagiousness and new A958D mutation of SARS-CoV-2 in children: An observational cohort study. (October 2021) - chen, Yinghu; Yao, Hangping; Fu, Junfen; Shu, Qiang; Chen, Zhimin; Wu, Nanping; Ye, Sheng; Wang, Wei; Ni, Yan; Shang, Shiqiang; Li, Wei; Zheng, Jishan; et al.
Abstract: Aims: To explore the contagiousness and new SARS-CoV-2 mutations in pediatric COVID-19. Methods: This cohort study enrolled all pediatric patients admitted to 8 hospitals in Zhejiang Province of China between 21 January and 29 February 2020, their family members and close-contact classmates. Epidemiological, demographic, clinical and laboratory data were collected. Bioinformatics was used to analyze the features of SARS-CoV-2. Individuals were divided into 3 groups by the first-generation case: Groups 1 (unclear), 2 (adult), and 3 (child). The secondary attack rate (SAR) and R0 were compared among the groups. Results: The infection rate among 211 individuals was 64% (135/211). The SAR in Groups 2 and 3 was 71% (73/103) and 3% (1/30), respectively; the median R0 in Groups 2 and 3 was 2 (range: 1-8) and 0 (range: 0-1), respectively. Compared with adult cases, the SAR and R0 of pediatric cases were significantly lower (p<0.05). We obtained SARS-CoV-2 sequences from the same infant's throat and fecal samples at a two-month interval and found that the new spike protein A958D mutation detected in the stool improved thermostability theoretically. Conclusions: Children have lower ability to spread SARS-CoV-2. The new A958D mutation is a potential reason for its long residence in the intestine.